How Do Cortical Excitatory Neurons Terminate Their Migration at the Right Place? Critical Roles of Environmental Elements - Hatanaka, Yumiko; Hirata, Tatsumi (Frontiers in Cell and Developmental Biology, 2020)
Interactions between neurons and their environment are crucial for proper termination of neuronal migration during brain development. In this review, we first introduce the migration behavior of cortical excitatory neurons from neurogenesis to migration termination, focusing on morphological and behavioral changes. We then describe possible requirements for environmental elements, including extracellular matrix proteins and Cajal–Retzius cells in the marginal zone, radial glial cells, and neighboring neurons, to ensure proper migration termination of these neurons at their final destinations. The requirements appear to be highly linked to sequential and/or concurrent changes in adhesiveness of migrating neurons and their surroundings, which allow the neurons to reach their final positions, detach from substrates, and establish stable laminar structures.